Poster 105: Nanowarming by Inductive Heating of Vitrified Large Articular Cartilage Specimens, In Vivo Testing with Hanford Mini Pigs. Issue 7 (30th July 2022) - Chen, Peng; Wang, Shangping; Chen, ZhenZhen; Greene, Beth; Helke, Kristi; Wu, Yongren; Slone, Harris; Brockbank, Kelvin; Yao, Hai; Goodloe, Jonathan
Objectives: There are limited resources of fresh cartilage osteochondral allografts. The short cartilage storage time using the gold standard hypothermic method further challenges the availability of fresh grafts due to the extended time needed for the surgical preparation. Therefore, there is a great need for a long-term cartilage preservation technique. Vitrification, a process that converts a liquid solution into a glassy solid without ice formation, is a promising technique for tissue cryopreservation.that enables the long-term storage of the cartilage tissue, potentially allowing better utilization of the grafts. Vitrification has generally been limited to small articular cartilage specimens ≤ 10 mm in < 3 mLs of cryoprotectant solution with a combined thickness < 1 cm. Cryopreservation of large articular cartilage samples has not previously been achieved. A major hurdle is ice formation caused by the slow warming rate with large vitrified specimens during the rewarming process in a liquid bath. Recently, a novel nanowarming technique in which radiofrequency excited magnetic nanoparticles (mNP) surrounding the tissues generate heat was developed. Compared to the conventional warming method, this technique can increase the warming rate by an order of magnitude or more, allowing fast and uniform heating of large tissue specimens in up to 50 mL volumes in a 3 cm wide tube. Systematic investigation of nanowarming benefits for cartilage preservation was performed using a series of tissue viability and biomaterial tests in in vitro testing with promising results. The researchers then developed a pig implant model to evaluate the efficacy of nanowarmed vitrified grafts for osteochondral transplantation in Hanford Pig Knees using a systematic investigation to evaluate histology and advanced imaging findings for incorporation in the graft. The authors hypothesized that the vitrified osteochondral allografts with subsequent nanowarming would perform similarly to fresh, frozen osteochondral grafts in terms of graft incorporation, graft viability, and cartilage properties. Methods: Femoral weight bearing condyles of sexually mature domestic Yorkshire cross pigs were obtained and no animals were sacrificed specifically for this study. Osteochondral pieces of the femoral condyle were harvested and separated into three groups: fresh, convection and nanowarming. The osteochondral pieces in the fresh group were kept in a Dulbecco's minimum essential media while convection and nanowarming specimens were both vitrified ± 2 mg/mL Fe nanoparticles. The vitrified tissues of the were then cooled and rewarmed using either a two stage convective warming process while the nanowarming group was rewarmed in 80 seconds using a solid state induction power supply. Cell viability (using fluorescence live/dead staining with calcein AM and ethidium homodimer) and metabolic activity (using alamarBlue assay) were then assessed among the three groups. In the in vivo study (approved by MUSC IACUC), 6 mm osteochondral plugs were harvested from the fresh and nanowarmed bulk osteochondral trochlea, and implanted in the trochlea of Hanford miniature pigs. After 4-month post-transplantation, the knee with implants was harvested and imaged with both µCT and MRI. The in vitro results were examined for significant difference using one/two-way ANOVA. A p-value < 0.05 indicated statistical significance. Results: AlamarBlue™ assay results showed VS83 (N = 4) outperformed VS70 (N = 3) for cartilage cryopreservation. The best cell metabolic activity was found in the nanowarming group with VS83 that fully recovered to fresh control values after 2 days of tissue culture. Live/dead staining confirmed that VS83 nanowarmed cartilage had many more live cells than the convection cartilage. Additionally, the cartilage electrical conductivity was similar among the fresh (N = 11), convection (N = 10), and nanowarming (N = 13) groups for both isotonic and hypotonic conditions. Fixed charge density calculated via the two-point conductivity measurements also revealed no significant difference among the three groups (Fig. 2a). Indentation results showed slightly higher equilibrium contact modulus in the cartilage surface layer of the nanowarming group (650.6 ± 134.7 kPa) than the convection group (567.7 ± 50.3 kPa) (No significance, N = 5 each group). Interestingly, aggregate modulus in nanowarming (326.7 ± 124.5 kPa, N = 14) and convection (334.6 ± 145.1 kPa, N = 7) groups were comparable and both significantly lower than the fresh (577.0 ± 229.6 kPa, N = 9) group via full thickness cartilage confined compression tests (p < 0.05), while no significant differences were found in permeability. Computational modeling results demonstrated a depth-dependent warming profile in the cartilage: the surface layer was warmed much faster than the deep zone. An in vivo pig model was successfully developed. Fresh graft implant was well integrated with the surrounding cartilage and bone tissues while connective tissue formation and partial bone loss were observed at the nanowarmed graft implant site. Conclusions: The live/dead staining and cell activity results indicated that nanowarming outperformed the conventional convection warming method by rescuing more cells and maintaining cell activity for large cartilage cryopreservation. Nanowarming caused very limited alterations on the cartilage permeability with conductivity results as well. This study pioneers the application of nanowarming for large sized articular cartilage cryopreserved specimens. In vivo results demonstrated the successful development of the pig implant model. Ongoing studies are trying to further optimize the vitrification, nanowarming, and implantation protocols to achieve translation of cryopreserved osteochondral grafts to clinical practice.